(untitled) (International journal of artificial intelligence, 2025)
The article analyzes the essence of family upbringing, its role in social life, and its importance in shaping a child’s personality. The family is considered the primary educational environment where parental affection, mutual respect, national values, and traditions play a crucial role. Particular attention is given to the authority of parents, their pedagogical knowledge, and cooperation with schools and local communities in the process of family upbringing. The article also highlights parental responsibility, the duty of raising children as well-rounded individuals, and the role of respect and reverence in strengthening the family environment. The family is viewed as the foundation of personal happiness and social stability.